Effects of substrate curvature radius, deposition temperature and coating thickness on the residual stress field of cylindrical thermal barrier coatings - Mao, W.; Jiang, J.P.; Zhou, Y.C.; Lu, Chungsheng (Elsevier S.A, 2011)
In a thermal barrier coating (TBC) system with cylindrical geometry, the position of coating plays an important role in the distribution of residual stress. In this paper, the residual stress field in three different types of TBCs with cylindrical geometry has been analyzed. The main focus is on the effects of substrate curvature radius, deposition temperature and coating thickness on the residual stress distribution during a deposition process. The results show that the substrate curvature radius significantly affects the distributions of radial and hoop residual stresses, which are in good agreement with experimental measurements by photo-stimulated luminescence piezospectroscopy (Wang et al., Acta Mater., 2009, 57(1):182–195). The maximum radial residual stress locates closely to the coating/thermal grown oxide interface. However, the maximum hoop residual stress lies in the thermal grown oxide layer, which is much more than other three layers and presents a strong stress singularity along the thickness direction.